Coping Mechanisms and Adaptation Strategies for Students in Online Education in Romania: Array - Negut, Camelia Nicoleta (New Trends in Psychology, 2021)
In the context of the COVID-19 pandemic and the increased risk of increasing the infection rate, all forms of education have undergone organizational changes, including the transition to education on the online platform. This measure was a novelty for Romanian education, which generated less desired, or less beneficial effects among participants in the educational process in Romania, both among students and teachers. The lack of physical contact, the physical presence in classes generated a stressful situation regarding the adaptation to the new form of development of the educational act with the help of the technological resources which in turn were a great challenge for both students and teachers. All these changes in logistics and infrastructure have determined the actors involved in the educational act to resort to specific coping mechanisms and strategies to adapt to the new educational trend.